Analisis Larangan Tadlis, Ihtikar, dan Ghulul dalam Perspektif Nabi Muhammad SAW: (Studi Kasus Korupsi Pertamina 2025) - Rubby Aziz Zaura Kamal; Iqbal Abdul Azis; Vivi Firda Silvia; Lina Marlina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Islam, as a perfect religion, teaches the values of honesty, justice, and transparency in various aspects of life, including economics and business. The prohibition of Tadlis (fraud in transactions), Ihtikar (hoarding goods for unfair profit), and Ghulul (corruption or betrayal of public trust) has been emphasized by Prophet Muhammad (PBUH) to protect society from harmful economic practices. This study aims to analyze the 2025 Pertamina corruption case from the perspective of Islamic prohibitions against Tadlis, Ihtikar, and Ghulul. This research employs a qualitative approach using a case study method, relying on secondary data from scholarly journals, news articles, and other relevant literature. The findings reveal that the corruption case reflects Tadlis through the manipulation of fuel quality information, Ihtikar through unfair price control, and Ghulul through the misappropriation of public funds, resulting in state losses amounting to trillions of rupiah and eroding public trust in the government. The study highlights that corruption is not only a violation of state law but also a moral crime that contradicts Islamic principles. The application of Islamic legal values, such as Ta’zir sanctions in the form of fines, asset confiscation, and severe punishments, can serve as preventive and repressive measures against corruption. Thus, this study aims to contribute to strengthening anti-corruption policies based on Islamic ethics while promoting transparency and justice in national economic governance.